The Value of Say on Pay - Kind, Axel; Poltera, Marco; Zaia, Johannes (My University, 2019)
This paper measures the influence of "say on pay" (SoP) - mandatory shareholder votes on top-management compensation - on the market value of corporate voting rights. By exploiting the staggered introduction of SoP regulations across ten major European economies, we show by difference-in-differences (DiD) regressions that the value of voting rights at annual shareholder meetings - extracted from prices of liquid options - has increased for firms with excessive CEO pay, while it has decreased for other companies. Surprisingly, shareholders tend to value advisory SoP votes but not the stricter binding votes. Thus, the option to signal dissent with current compensation via SoP votes is not per se valuable and can actually translate into net costs for shareholders. Finally, the effect of mandatory SoP on voting values is concentrated on the year of introduction and fades out over time. Placebo regressions support the accuracy of our DiD research design.
Keywords: Say on Pay, Corporate Voting Rights, Corporate Governance, Option Pricing; 330